Associative monotonic commutative operator (AMC) UV - Umit Ertugrul (Communication in Mathematical Modeling and Applications, 2017)
Uninorms and nullnorms are associative monotonic and commutative operators. In this study, an operator UV is defined by uninorm U and nullnorm V and showed that UV satisfies associativity, monotonicity and commutativity properties. And it is showed that UV does not have neutral element and have zero element if U is disjunctive uninorm on [0,k]. Moreover, it is show that if it is taken smallest uninorm and nulnorm, UV is also smallest AMC operator.